Pelatihan Diversifikasi Olahan Ikan Nila (Oreochromis niloticus) bagi Tim Penggerak PKK Kecamatan di Kota Semarang - Tri Rettagung Diana; Esteria Priyanti; Ira Handayani (ABDI KARYA : Pengabdian Kepada Masyarakat, 2024)
In line with the government program from the Semarang City Fisheries Service regarding the diversification of processed fish, therefore Culinary Arts Study Program of AKS Ibu Kartini took a good opportunity to collaborate with the Semarang City Fisheries Service. The form of collaboration carried out was holding training activities on the diversification of processed tilapia fish for PKK Team of Districts in Semarang City. The aim of this training is that participants can process and serve coconut layer tilapia products, crispy tempeh tilapia, tilapia muffins, tilapia puff tacos and tilapia fusilli. These five products use fresh tilapia fish as the basic ingredient. The number of participants who attended this training was 25 people. The method used in this training consists of interactive lectures, cooking classes, questions and answers, and product evaluations produced by participants. The training activities on the diversification of processed tilapia fish that have been carried out can help improve the skills of PKK Team from Districts in Semarang City. This is demonstrated by the active participation of all participants, and the products produced by all participants are in accordance with the established criteria standards. Thus, it can be concluded that all participants were able to process and serve coconut layer tilapia, crispy tempe tilapia, tilapia muffins, tilapia puff tacos and tilapia fusilli products well.